Loads acting on the locomotive system of professional female volleyball players during the landing phase of spikes and blocks - Kabacinski, J.; Dworak, L. B.; Kmiecik, K.; Murawa, M.; Maczynski, J. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to identify force and time characteristics of ground reaction forces produced during the landing phase of volleyball technical elements: blocks and spikes. Applying piezoelectric dynamometry and video recording, a series of tests were carried out with the participation of four female volleyball players of the first team of AZS AWF sports club competing in the Female Volleyball League. The recorded force vs time line graphs of ground reaction Rx(t), Ry(t) and Rz(t) were used to calculate the values of kinematic-dynamic parameters that describe the level of dynamic loads. Results show that the majority of loads in these movement tasks is significant and may be traumatogenic.